2012
DOI: 10.1021/ja307308j
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles as Electronic Bridges for Laccase-Based Biocathodes

Abstract: Direct electron transfer (DET) reactions between redox enzymes and electrodes can be maximized by oriented immobilization of the enzyme molecules onto an electroactive surface modified with functionalized gold nanoparticles (AuNPs). Here, we present such strategy for obtaining a DET-based laccase (Lc) cathode for O(2) electroreduction at low overpotentials. The stable nanostructured enzymatic electrode is based on the step-by-step covalent attachment of AuNPs and Lc molecules to porous graphite electrodes usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
181
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(189 citation statements)
references
References 61 publications
6
181
2
Order By: Relevance
“…[187] SAM-functionalized gold electrodes and gold nanoparticles (NPs) with anthracenethiol derivatives, [188] or phenyl groups ending either with amino or carboxyl functions were also evaluated as platforms for efficient orientation of Trametes versicolor (Tv), Tt and Trametes hirsute (Th) LACs. [189][190][191] PMIRRAS, QCM, and electrochemistry were coupled and allowed a specific orientation linked to a different activity of the enzyme depending on the functionality borne by the SAM to be demonstrated. [189] The authors also demonstrated a clear correlation between the orientation of LAC with a b-sheet tilted with respect to the electrode surface and the electrocatalytic activity.…”
Section: Multicopper Oxidases (Mcos)mentioning
confidence: 99%
“…[187] SAM-functionalized gold electrodes and gold nanoparticles (NPs) with anthracenethiol derivatives, [188] or phenyl groups ending either with amino or carboxyl functions were also evaluated as platforms for efficient orientation of Trametes versicolor (Tv), Tt and Trametes hirsute (Th) LACs. [189][190][191] PMIRRAS, QCM, and electrochemistry were coupled and allowed a specific orientation linked to a different activity of the enzyme depending on the functionality borne by the SAM to be demonstrated. [189] The authors also demonstrated a clear correlation between the orientation of LAC with a b-sheet tilted with respect to the electrode surface and the electrocatalytic activity.…”
Section: Multicopper Oxidases (Mcos)mentioning
confidence: 99%
“…Various types of metal nanoparticles have been used in the production of nanocomposite hydrogels in the field of biomaterials including gold [14], silver [15] and other noble metal nanoparticles, while metal oxide nanoparticles such as iron oxide [16] and zirconia [17] have also been used. Since metal and metal oxide nanoparticles possess the desired electrical conductivity, magnetic properties, and antibacterial properties, nanocomposite hydrogels that contain metal or metal oxide nanoparticles are widely used in conductive scaffolds, electronic switches, actuators, and sensors [18][19][20][21]. Gold nanoparticles (AuNPs) are one of the most essential metal nanoparticles actively used in biomedical fields.…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…Accordingly, MCOs are good candidates for use as biosensing systems in implantable devices designed for real-time O 2 monitoring. In the present work, an electrochemical O 2 biosensor designed to work in acidic biofluids, using Trametes hirsuta laccase (ThLc) immobilised covalently on a low-density graphite (LDG) electrode by use of a two-step immobilisation strategy is detailed (Vaz-Dominguez et al, 2008;Gutierrez-Sanchez et al, 2012). LDG is a suitable support for ThLc immobilisation due to its high porosity and ready functionalisation, especially since its surface similarity with polyphenols enhances the orientation process with the T1 site facing the electrode.…”
mentioning
confidence: 99%
“…Cyclic voltammograms of the modified electrodes for O 2 reduction were recorded in the range of 0.8-0 V vs Ag/AgCl at a 10 mV s −1 scan-rate in 100 mM acetate buffer (pH 4.2) containing 100 mM NaClO 4 enriched in O 2 by passing the gas through for 10 min prior to the measurement. The modified electrode shows the typical cathodic response for a LDG/ThLc electrode starting at 0.6 mV vs Ag/AgCl (Vaz-Dominguez et al, 2008;Gutierrez-Sanchez et al, 2012), whereas a LDG electrode modified only with the aminoaryl layer (NH 2 /LDG) exhibits no O 2 reduction ability.…”
mentioning
confidence: 99%
See 1 more Smart Citation